IMPLEMENTASI PENCEGAHAN DAN PENANGGULANGAN HUMAN IMMUNODEFIENCY VIRUS (HIV) DAN ACQUIRED IMMUNODEFIENCY SYNDROME (AIDS) DI KOTA PEKANBARU - Rhival Metra; Mimin Sudari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
HIV and AIDS is one of the most global public policy issues that can threaten the life of society so as to cause casualties, social impact as well as the psychological impact. Pekanbaru is the most common area of HIV and AIDS cases compared to other areas in Riau Province. The purpose of this study indicate the results of the implementation of the prevention and control of HIV and AIDS in the city of Pekanbaru and showed limitations in the implementation of prevention and control of HIV and AIDS as contained in Pekanbaru Mayor Regulation number 32 of 2013. This study uses the theory of policy implementation in Jan Merse (2015) which uses four indicators, namely: Information, Content Policy, Community Support and Distribution Potential. This study used qualitative methods which are located in the city of Pekanbaru. Informants of this research that the National AIDS Commission (KPA) Pekanbaru City, City Health Office Pekanbaru and other relevant agencies to conduct interviews, observation and documentation so on get the required data as the primary data and secondary data was then analyzed which shows the results of the implementation and limitations. The results of this study found that implementation of prevention and control of HIV and AIDS in the city of Pekanbaru has not been implemented to the fullest, implementor that is not optimally carrying out their duties, the problem of HIV that is not a priority, public opinion was still rubbing against the norm, and resources are very limited so the implementation process is not running optimally. Keywords: Implementation, Prevention, Mitigation